2010
DOI: 10.1016/j.orcp.2010.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for gastroesophageal reflux disease in an impoverished minority population

Abstract: SummaryBackground and Aims-An epidemiological link between an increased body mass index and complaints of typical heartburn symptoms has been identified. It appears that increasing waist circumference, rather than overall weight is most important. Studies to date have not included minority, impoverished communities. Our aim was to determine the impact of obesity on the prevalence of reflux disease in an impoverished community while controlling for known confounders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…This is why we did not control for age in our analysis. We adjusted for physical activity [49], diabetes [50,51], BMI [52,53,54,55,56], and diet-related behaviors [57] in our analyses, as earlier studies have introduced these variables as contributing factors to GERD and FD.…”
Section: Discussionmentioning
confidence: 99%
“…This is why we did not control for age in our analysis. We adjusted for physical activity [49], diabetes [50,51], BMI [52,53,54,55,56], and diet-related behaviors [57] in our analyses, as earlier studies have introduced these variables as contributing factors to GERD and FD.…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study from New Zealand [5] and an Iranian study [6] reported similar poor association of GERD with the two obesity parameters. Other studies [1,2,7,8] have shown an increased prevalence of GERD in those with higher BMI. There are very few reports on BMI and WHR association with GERD symptoms.…”
mentioning
confidence: 87%
“…A study that was derived from a population registry in Australia (Pandeya et al, 2012) found no evidence that frequent GERD symptoms were associated with coffee consumption. Similarly, a cross-sectional survey acquired via in-home interviews, convenience sampling, and targeted mailing, found no association between reflux disease and lifestyle choices such as coffee drinking (Friedenberg et al, 2010). Two studies from Italy revealed no correlation between coffee drinking and GERD (Nasseri-Moghaddam et al, 2008;Conio et al, 2002).…”
Section: Sources Of Informationmentioning
confidence: 99%
“…The abstracts of all these articles were reviewed and 15 were original epidemiological studies that evaluated the relationship between GERD and coffee (Pandeya et al, 2012;Bhatia et al, 2011;Lee et al, 2011;Friedenberg et al, 2010;Nasseri-Moghaddam, et al, 2008;Dore et al, 2008;El-Serag et al, 2007;Zheng et al, 2007;Somi et al, 2006;Moraes-Filho et al, 2005;Nilsson et al, 2004;Wang et al, 2004;Castelo Vega et al, 2003;Conio et al, 2002;Chang et al, 1997). These articles were reviewed decrease in the risk of reflux symptoms among people who drank more than seven cups of coffee per day compared with those who drank less than one cup (OR: 0.6; 95% CI: 0.4 − 0.7).…”
Section: Sources Of Informationmentioning
confidence: 99%
See 1 more Smart Citation